Care and vulnerability in liminal spaces: a study of The Blind Matriarch - Dev, Pragya; Mishra, Binod (Penerbit Universiti Kebangsaan Malaysia, 2025)
In this article, we address the nuanced treatises on care in light of Namita Gokhale’s The Blind Matriarch (2021). With the aim of liberating care from its archaic association with feminine attributes and unidirectional dependency, we politicise and situate it alongside universal and continuous vulnerability (Butler, 2009), affecting and assorting human precariousness. Our understanding of care as a discourse entails an investigation of human and non-human relationality in a myriad of spaces. As demonstrated in the aforementioned text, the pandemic evinces the shredding of unvarying lives of the residents of house no. C100- with extended lockdowns and uncertainties hanging in the air, everybody starts noticing the puny. Tapping into these mundane aspects, the characters of the novel can be understood as assemblages interacting with care, all the while exposing the 'universal, inevitable condition of humanity' (Fineman, 2010), i.e., vulnerability at multiple fronts. By employing the concept of ‘care’ and ‘vulnerability studies’, this article examines the pandemic as a finite ‘event’ in both temporal and spatial scope, yet one that encompasses diverse entities. The findings situate Gokhale’s The Blind Matriarch as a seminal text for understanding the precarious human condition during the pandemic and further advocate for a new episteme that prioritises care and vulnerability as integral to literary analysis.